Carcass Quality of Different Meat - Typed Chickens When Achieve a Common Physiological Body Weight - Liu, Fuzhu; Niu, Zhuye (International Journal of Poultry Science, 2008)
This experiment was conducted to compare carcass characteristics of native quality chicken white Lueyang (WL), modern commercial broiler strain Arbor Acres breeder (AA) and their respective F1 cross when achieve a common live body weight. A total of 300 day-old chicks were allotted to three groups and reared under the same conditions until they reached market weight (1800±20 g) respectively, then ten of individual male birds from each group were killed for measuring. There were significant differences in carcass and meat characteristics for breeds at a common market weight. WL had a large age to market weight, lower abdominal fat weight, lower breast meat yield, higher leg meat yield (P<0.05 or P<0.01). moisture and lipids of both breast muscle and thigh muscle were lower for WL than AA (P<0.01), but protein and ash components of both breast muscle and thigh muscle were higher for WL than AA (P<0.05 or P<0.01). Muscle pH24h was higher for WL than AA (P<0.05). WL had a lower L* value than AA and their F1 (P<0.05), but a higher a* value and b* value (P<0.01). The F1 crosses appeared to have characteristics more like AA for carcass and meat characteristics.